Trade, value chain technology and prices: Evidence from dairy in East Africa - Ignowski, Liz; Minten, Bart; Van Campenhout, Bjorn; Vandevelde, Senne (Oxford University Press, 2022)
Differences in world market participation and access to value chain technologies have resulted in uneven experiences across countries. In this paper, we explore their impact on prices in the value chain, using the example of Ethiopia and Uganda. We develop a conceptual framework, then validate the model using primary price data collected at several levels in the dairy value chains in both countries. We find that prices are lower in Uganda than Ethiopia, reflecting their respective net trade status. Moreover, despite shorter value chains, we find much more significant effects of distances from the capital on milk prices in Ethiopia than in Uganda. This is linked to the presence of milk chilling centers in Uganda. While such technology is important for milk quality, we find here that they also have the added benefit to reduce the impact of farmer's remoteness on prices and allow for more geographically extended value chains.